Exploring EFL Students’ Responses to Learning Speaking Through Ted Talk Videos: A Case Study Approach - Fitriyani, Sandra Dewi; Kusrin, Kusrin; Ambarwati, Evi Karlina (FKIP-Universitas Riau, 2024)
Effective communication plays a crucial role in daily life, and technology has significantly influenced students' speaking skills by providing engaging and convenient learning tools, such as TED Talk videos. This study explores students' independent learning in speaking and evaluates their responses to using TED Talks as a medium for English as a Foreign Language (EFL) education. A qualitative case study approach was employed, utilizing observations, reflective journals, and semi-structured in-depth interviews for data collection. Thematic analysis was used to interpret the data. The findings indicate that most students responded positively to using TED Talks for learning spoken English. Students reported increased motivation, exposure to new vocabulary, improved pronunciation, and positive learning experiences from the speakers. Furthermore, the variety of topics in TED Talks contributed to an engaging and diverse learning environment. In conclusion, TED Talks serve as an effective tool for enhancing EFL learners' speaking skills.